EQUIPPING A SOCIAL AND DOMESTIC ORIENTATION ROOM IN SPECIALIZED BOARDING SCHOOLS FOR MENTALLY RETARDED CHILDREN WITH DEVELOPMENTAL DISABILITIES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article substantiates the need to comply with safety, functionality, flexibility and correctional and pedagogical requirements when organizing a socio-domestic orientation room. The results of the study are important in ensuring the social adaptation of mentally retarded children, preparing them for independent life and integrating them into an inclusive society.